Medical image steganography using priority queue with Elgamal cryptosystem. (2016) - Jain, Mamta; Kumar, Anil
This paper describes a methodology for hiding medical records and patient's identity information inside their scan medical image files using the concept of dynamic priority queue least significant bits (LSBs) substitution. Elgamal cryptosystem is used to encrypt patient's sensitive data. The outcome of the cryptosystem is organised in various priority queue blocks and sub blocks based on a secret data length of each block. The cipher text is obtained from priority queue as highest priority (weight) data will be retrieved first. Now embed the cipher text in a medical cover image at 7th bit or 8th bit position using heap-LSB technique. Authorised receiver can retrieve the correct plain text using private keys. Performance analysis is observed using various performance measure parameters between various medical stego and cover images. Results are analysed and compared with many of existing steganography algorithms.